2019
DOI: 10.3390/ncrna5010026
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA in Vascular Disease and Aging

Abstract: Cardiovascular diseases are the most prominent cause of death in Western society, especially in the elderly. With the increasing life expectancy, the number of patients with cardiovascular diseases will rise in the near future, leading to an increased healthcare burden. There is a need for new therapies to treat this growing number of patients. The discovery of long non-coding RNAs has led to a novel group of molecules that could be considered for their potential as therapeutic targets. This review presents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 118 publications
(152 reference statements)
0
24
0
5
Order By: Relevance
“…There is an increasing body of evidence showing that long noncoding RNAs (lncRNAs) and micro RNAs (miRNAs) are involved in cardiovascular aging. LncRNAs act as key regulators of the central aspects of cardiovascular aging (i.e., cardiac hypertrophy, fibrosis, and endothelial/vascular function), and their role in cardiac biology has been recently reviewed [51][52][53][54][55]. A number of miRNAs have been associated with regulation of senescence in various tissues, including the heart [56,57].…”
Section: Cardiac Senescencementioning
confidence: 99%
“…There is an increasing body of evidence showing that long noncoding RNAs (lncRNAs) and micro RNAs (miRNAs) are involved in cardiovascular aging. LncRNAs act as key regulators of the central aspects of cardiovascular aging (i.e., cardiac hypertrophy, fibrosis, and endothelial/vascular function), and their role in cardiac biology has been recently reviewed [51][52][53][54][55]. A number of miRNAs have been associated with regulation of senescence in various tissues, including the heart [56,57].…”
Section: Cardiac Senescencementioning
confidence: 99%
“…The mechanistic role of microRNAs (miRNAs, miRs) in cardiovascular pathophysiology is well established. [1][2][3] Substantial evidence has shown that miRNAs can be included in extracellular microvesicles/exosomes, thereby protecting them from ribonuclease-dependent degradation, allowing cell-cell communication. [4][5][6] Cardiac fibroblasts and their activated counterpart (myofibroblasts) have emerged as essential cellular components of normal and postischemic cardiac function.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNA (lncRNA) refers to a class of RNA molecules of more than 200 nucleotides in length which are not translated to proteins. [6][7][8] These special RNA molecules are produced via transcription from intergenic regions of the genome, from within introns of protein-coding genes, or from the antisense strand of a given gene.…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence supports the notion that lncRNAs may have important roles in regulating gene expressions, and their functions can be either stimulatory or inhibitory. [6][7][8] The principal molecular mechanisms by which lncRNAs regulate gene expressions include the following: (a) lncRNAs may bind to conventional transcription factors or chromatin-modifying enzymes (such as polycomb 1 repressive complex, histone demethylases, and DNA methyltransferases). 9 This in turn can result in different circumstances.…”
Section: Introductionmentioning
confidence: 99%